Mistrust -- Ethnographic Approximations - Mühlfried, Florian (Kultur und soziale Praxis, 2018)
Scholars have long seen trust as a foundational social good. We therefore have ample studies on building trust in free markets, on cultivating trust in the state, and on rebuilding trust through civil society. The contributors to this volume, instead, take a step back. They ask: Can mistrust ever be more than the flip side of trust, more than the sign of an absence or failure? By looking ethnographically at what a variety of actors actually do when they express mistrust, this volume offers a richly empirical trove of the social life of mistrust across a range of settings.